Evidence-based recommendations to support elite athletes during preconception and pregnancy: A modified Delphi survey of elite Australian athletes and key stakeholders - Titovaa, J.; Davenportb, M. H.; Hayman, M. (Journal of Science and Medicine in Sport, 2025)
Objectives Pregnancy policies have been identified as a critical support for elite athletes during preconception and pregnancy. However, many sporting organisations lack such policies and the resources to create them. This study aimed to establish consensus of evidence-based policy and practice recommendations for supporting preconception and pregnancy in Australian elite athletes.